Histomorphological Changes in Human Senile Cataractous Lenses with Diabetic and Non-Diabetic Patients: A Comparative Study (Medical Forum Monthly, 2021)
Objective: To determine the histomorphological changes in the human senile cataract. between diabetic and non-diabetic eyes and the correlation between anterior ocular segment biometry and HbA1c level.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Anatomy with collaboration of Sindh Institute of Ophthalmology and Visual Sciences (S.I.O.V.S) @ Eye Hospital Hyderabad, Sindh for the period of six months from April 2020 to October 2020.Materials and Methods: This study was conducted on 385 patients aged more than 40 years who underwent intra-capsular cataract extraction who were included in study while those patients whose age less than 40 years. Data were analyzed using SPSS version 22.0Results: A total of 385 patients of senile cataract extraction were selected. The frequency of cataracts was found 107(27.79%) among diabetics’ patients. There was a statistically significant difference concerning the increased incidence of senile cataract with HbA1C (mg/dL) in diabetic patients as compared to non-diabetic patients (p-value = <0.0001). The calcareous change was noted in 5 cases of 40 to 100 years’ age. Calcarious change and Collagen bundles were noted out of 278 cases of non-diabetic of 40 to 100 years’ age.Conclusion: Duration of diabetes, age, and gender were found to be significant risk factors for predicting the grade of cataract in male or female diabetic patients.